Evaluation of Vegetative Growth of Local Avocado Plants after the Grafting Process with Avocado Butter - Riska Nabila; Muhammad Yusuf (MultiTech Publisher, 2023)
This study investigated the effectiveness of grafting butter avocado scions onto local avocado rootstocks as a vegetative propagation method. This research was carried out for four weeks with equipment such as scissors, knives, and polybags used to carry out the grafting procedure, and careful monitoring was carried out to assess plant development. Although the first week showed little change, the fourth week showed promising shoot growth, indicating successful grafting. Existing challenges, including humidity and leaf discoloration, have been appropriately addressed. This study concludes that grafting is feasible for propagating local avocado plants if carried out carefully and adequately after grafting. Regular monitoring and careful maintenance are recommended to ensure optimal plant growth to improve avocado cultivation in productivity and fruit quality.